Bilateral Multiple Mastoid Foramina Along With a Unilateral Occipito Mastoid Canal in an Adult Skull of North Indian Origin-A Rare Variation - Sehmi, Seema (Academia Anatomica International, 2017)
The mastoid part of the temporal bone on its lateral surface usually has a mastoid foramen through which mastoid emissary vein and dural branch of the occipital artery passes. The foramen varies both in number as well as location. It can either be in the temporal or parietal bone, occipito mastoid suture or parieto mastoid suture. On routeine osteology class in the department of Anatomy, SGRD Medical college, Amritsar, an adult human skull of North Indian Origin was found to have multiple mastoid foramina on both sides. There was a bony ossicle seen on the left side connecting tip of mastoid process to the occipital condyle of left side creating a bony canal can be named as occipitomastoid canal. This variation can have great clinical as well as surgical significance during neurological and oto laryngeal surgery. The knowledge of this variation will contribute to the epigenetic and anthropological study of the minor variations related to the mastoid foramen.